2021
DOI: 10.3390/microorganisms9112313
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Stress Tolerance of a C4 (Zea mays L.) and C3 (Vigna radiata L.) Plants Primed with UV and Gamma-Treated Bacillus subtilis

Abstract: Chromium stress is one of the deleterious abiotic factors that reduce crop production. Two anatomically different crops (C3 and C4) were compared for their chromium (0 and 50 ppm) tolerance and responses towards Bacillus subtilis (B. subtilis). Strains of B. subtilis were exposed to UV (30–210 min) and gamma irradiation (1–4 KGy), and the best mutants were selected on petri plates containing selective markers. Maize and mungbean were supplied with selected strains or the parent strain in rooting medium, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Many studies have demonstrated that heavy metals reduce plant nutrient uptake and accumulation (Shahzad et al 2021). Micronutrient solubility, soil uid pH, soil nutrient physicochemical characteristics, and the presence of complex formation on the surfaces of both inorganic and organic material are all factors that affect the bioavailability of minerals in chromium containment soils (Banik et al 2019, Hayat et al 2010).…”
Section: Patle Et Al 2018)mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that heavy metals reduce plant nutrient uptake and accumulation (Shahzad et al 2021). Micronutrient solubility, soil uid pH, soil nutrient physicochemical characteristics, and the presence of complex formation on the surfaces of both inorganic and organic material are all factors that affect the bioavailability of minerals in chromium containment soils (Banik et al 2019, Hayat et al 2010).…”
Section: Patle Et Al 2018)mentioning
confidence: 99%
“…It belongs to the periodic table's group VI B of transition metals. Large amounts of chromium compounds are released into the environment as liquid, solid, and gas waste, mainly due to industrial processes such as tanning and chrome plating, which have detrimental biological and ecological effects (Kotaś &Stasicka 2000, Shahzad et al 2021). Mobilization, absorption, and toxicity of chromium in the plant system are all determined by the metal speciation that occurs due to metal contamination.…”
Section: Introductionmentioning
confidence: 99%